Kønsligt hierarki eller religiøs androgyni - Birgitte Graakjær Hjort (Religionsvidenskabeligt Tidsskrift, 2000)
Only a few texts from the New Testament have been used and misused as have 1 Cor 11:2-16. A widespread misreading of the pericope consists in the interpretation that Paul there argued against equality between men and women generally or in the context of worship. The purpose of this article is twofold: To demonstrate why this reading is untenable and to argue for a more proper interpretation. My reading is based on Paul’s line of argument, including his remarkable formation of the kephale-structure and the position of the pericope between chapters (8 and) 10 and 11:17-21, respectively, as well as on the letter as a whole. All these things together indicate that the problem under discussion was not the relationship between the sexes as such, but this relationship seen in a religious, ritual context. Paul reproved a conduct whose shamefulness lay in its threat to both the gender polarity according to the creation and the sovereignty of God, a conduct which may also have caused divisions in the community. What Paul was arguing against, was a syncretism whose hallmark was an emancipatory equalization of gender polarity and, maybe, ritual intoxication and whose religious precedent was to be found in the worshipping of idols. With this interpretation as the main criterion for testing different hypotheses put forward to explain the historical situation causing Paul to write the text, I have found that a possible reconstruction consists of an influence on the Corinthians from pre-gnostic thoughts in a broad sense, combined with a more specific influence from the cult of Dionysus.